Russia, the West, and the Ukraine crisis - Gotz, Elias (Routledge, 2018)
This book examines the causes and consequences of the Ukraine crisis, with a special focus on Russia's relations with the West. Towards that end, it brings together international relations scholars and area specialists. The contributors employ different theoretical approaches and offer partly complementary and partly competing analyses. In so doing, this book seeks to stimulate dialogue between different positions and advance our understanding of a topic that will shape the European security order for many years to come.